Pumping of concrete mixtures: rheology, lubrication layer properties and pumping pressure assessment - Vosahlik, Jan (Kansas State University, 2018)
Pumping is the most utilized placement technique to deliver fresh concrete from the concrete mixer to the formwork on construction site. Compared to other available placement methods, such as bucket-and-crane or conveyor belts, pumping offers superior placement rates while reducing the required labor cost. Despite the fact that concrete pumping has been utilized on job sites around the world since the early 1960s, there is still a lack of knowledge, supported by research evidence, as to what affects concrete pumpability and how pumping changes concrete properties both in the plastic and hardened state. A four-phase research study was carried out to: (1) improve the existing methodology of rheological characterization of the lubrication layer formed during pumping, (2) evaluate the effect of concrete mixture constituents and proportioning on rheological properties of concrete and the lubrication layer, (3) asses the effect of pumping and pumping pressure on concrete fresh properties and the air void system under controlled conditions, and (4) to evaluate the effect of pumping on concrete fresh properties and the air void system in the field conditions. In the first phase of this research program, a correction procedure was developed evaluating 3D flow at the bottom of the cylindrical concrete interface rheometer. Results showed that the correction procedure can be successfully used for characterization of lubrication layer properties, and that the bottom of the cylinder can cause measurement error of up to 10% depending on concrete rheological properties and the interface rheometer geometry. The second phase of this research program consisted of a laboratory study to evaluate rheological properties and properties of the lubrication layer of large variety of concrete mixtures. Considered mixture proportion variables included air void content, water-to-cement ratio, paste volume, fly ash replacement ratio, fine-to-coarse aggregate ratio, aggregate shape, use of viscosity-modifying admixture, and use of nano-clay particles. Results indicated that the changes in rheological properties of the lubrication due to mixture proportioning adjustments corresponded in most cases to changes of the bulk concrete rheological properties. In the third phase of the study, a full-scale controlled pumping experiment was conducted. During the experiment, three different concrete mixtures were pumped and both fresh and hardened properties of concrete were determined. Additionally, the pumping circuit was equipped with a system to monitor pumping pressures. The obtained results revealed that concrete pumping can significantly modify concrete fresh properties. Additionally, it was shown that changes in the fresh properties as well as in the concrete air void system are independent of applied concrete pressure. Finally, the forth phase of this research program consisted of field evaluation of concrete pumping. Six concrete bridge project sites were visited and concrete samples were collected before and after pumping. Analysis results indicated that the changes in concrete properties appear to be influenced not only by mixture characteristics but also by discharge conditions in the formwork.
Keywords: concrete; pumping; rheology